Ansofaxine hydrochloride inhibits tumor growth and enhances Anti-TNFR2 in murine colon cancer model - Jing, Qianyu; Wan, Quan; Nie, Yujie; Luo, Junqian; Zhang, Xiangyan; Zhu, Lan; Gui, Huan; Li, Linzhao; Wang, Chenglv; Chen, Shuanghui; Wang, Mengjiao; Yuan, Haohua; et al. (Frontiers in Pharmacology, 2023)
Introduction: As psychoneuroimmunology flourishes, there is compelling evidence that depression suppresses the anti-tumor immune response, promotes the progression of cancer, and inhibits the effectiveness of cancer immunotherapy. Recent studies have reported that antidepressants can not only alleviate the depressant condition of cancer patients, but also strengthen the anti-tumor immunity, thus suppressing tumors. Tumor necrosis factor receptor 2 (TNFR2) antagonistic antibodies (Anti-TNFR2) targeting tumor-infiltrating regulatory T cells (Tregs) has achieved great results in preclinical studies, and with a favorable toxicity profile than existing immunotherapies, and is expected to become a new generation of more effective treatment strategies. Understanding the effects of combination therapy with antidepressants and Anti-TNFR2 may help design new strategies for cancer immunotherapy. Methods: We treated CT26, HCT116, MCA38 and SW620 colon cancer cells with fluoxetine (0–50 µM), ansofaxine hydrochloride (0–50 µM) and amitifadine hydrochloride (0–150 µM) to examine their effects on cell proliferation and apoptosis. We explored the antitumor effects of ansofaxine hydrochloride in combination with or without Anti-TNFR in subcutaneously transplanted CT26 cells in tumor-bearing mouse model. Antitumor effects were evaluated by tumor volume. NK cell, M1 macrophage cell, CD4+ T cell, CD8+ T cell, exhausted CD8+ T and regulatory T cell (Tregs) subtypes were measured by flow cytometry. 5-hydroxytryptamine, dopamine and norepinephrine levels were measured by ELISA. Results: Oral antidepression, ansofaxine hydrochloride, enhanced peripheral dopamine levels, promoted CD8+T cell proliferation, promoted intratumoral infiltration of M1 and NK cells, decreased the proportion of tumor-infiltrating exhausted CD8+T cells, and strengthened anti-tumor immunity, thereby inhibiting colon cancer growth. In combination therapy, oral administration of ansofaxine hydrochloride enhanced the efficacy of Anti-TNFR2, and produced long-term tumor control in with syngeneic colorectal tumor-bearing mice, which was attributable to the reduction in tumor-infiltrating Treg quantity and the recovery of CD8+ T cells function. Discussion: In summary, our data reveal the role of ansofaxine hydrochloride in modulating the anti-tumor immunity. Our results support that exhausted CD8+T is an important potential mechanism by which ansofaxine hydrochloride activates anti-tumor immunity and enhances anti-tumor effects of anti-TNFR2.